FOR RELIABILITY ASSESSMENT OF STEEL , LATTICE TOWER RESISTANCE CONNECTION IN COMPLEX ROD SYSTEMS - , С. Ф., А. В. (Municipal economy of cities. Series: «Economy science», 2013)
We consider some approaches to calculating the reliability of steel lattice towers as complex rod systems . The estimation of reliability of the spatial sections of triangular and rectangular cross-section with different types of grids, are formulas of probability of failure of spatial sections if rivnonadiynosti their elements. Analyzed depending on the probability of failure of the whole tower on the reliability of individual sections of the assumption of independence of failures.